2018
DOI: 10.1038/s41598-017-18712-0
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Study on Disconnection Events in Comets

Abstract: When comets interacting with solar wind, straight and narrow plasma tails will be often formed. The most remarkable phenomenon of the plasma tails is the disconnection event, in which a plasma tail is uprooted from the comet’s head and moves away from the comet. In this paper, the interaction process between a comet and solar wind is simulated by using a laser-driven plasma cloud to hit a cylinder obstacle. A disconnected plasma tail is observed behind the obstacle by optical shadowgraphy and interferometry. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Brandt et al (1999) and Brandt and Snow (2000) also concluded this effect using observations of comets 1P/Halley, 122P/de Vico, C/1996 B2 Hyakutake, and C/1995 O1 Hale-Bopp. Li et al (2018) performed laboratory experiments to study tail detachment events. They used a laser-driven plasma which collides with a cylindrical obstacle.…”
Section: Magnetic Reconnectionmentioning
confidence: 99%
“…Brandt et al (1999) and Brandt and Snow (2000) also concluded this effect using observations of comets 1P/Halley, 122P/de Vico, C/1996 B2 Hyakutake, and C/1995 O1 Hale-Bopp. Li et al (2018) performed laboratory experiments to study tail detachment events. They used a laser-driven plasma which collides with a cylindrical obstacle.…”
Section: Magnetic Reconnectionmentioning
confidence: 99%